Emotional interaction with a mobile robot using hand gestures - Young-Hoon Nho; Ji-Won Seo; Woo-Jin Seol; Dong-Soo Kwon (2014 11th International Conference on Ubiquitous Robots and Ambient Intelligence (URAI), 2014)
Interaction between a human and a robot can have positive effects on temperament and the development of children and can also be beneficial during psychotherapy. When a robot finishes a task, a user may want to give the robot a reward by means of emotional interaction. Here, we assume that a mobile robot is capable of emotional interactions. We design a mobile robot system which interacts with humans through the use of a LeapMotion sensor for elaborate hand gesture tracking. The designed mobile robot system combines emotional modeling and hand gesture tracking. From this, the user can express emotions and intentions using two hands at the same time. The left hand controls directions (forward, backward, right, left, and stop) and the right hand controls emotions (calm, proud, angry, passive, and depressed). If the user wants the robot to move upon a user command, the user should always consider the emotion and energy of the robot because it can move in the opposite direction or weakly when the emotion and energy levels are low. This study outlines how human can interact with a robot using intuitive hand gestures.